LAYANAN PEMAKAMAN MEWAH MUSLIM: KOMODIFIKASI DAN REINTERPRETASI PEMAKAMAN - Rafi Akhbar Kurniawan; Sujadi Sujadi (Jurnal Analisa Sosiologi, 2024)
This article examines the phenomenon of luxury Muslim funerals in Indonesia that reflects the negotiation between traditional Islamic values and modernity among middle-class Muslims. Using a qualitative approach, this study explores how the commodification of religious values affects funeral practices and the meaning of death. The study found that luxury funeral services such as Al-Azhar Memorial Garden not only offer exclusive facilities, but also integrate religious values and social status symbols through modern narratives that are in accordance with Islamic law. Luxury funerals become symbolic spaces that represent piety, class identity, and modern lifestyle aspirations. Moreover, the reinterpretation of funerals and death by middle-class Muslims indicates a self-transformation that reinforces religious practices in daily life. Thus, this phenomenon reflects the complex social dynamics between religiosity, materialism and modernity in urban Muslim society.